Payment for ecosystem services (PES): a holistic tool for sustainable forest management-a case study from Pakistan - Muhammad,S. (2023)
Abstract Economic valuation of ecosystem services is a new concept in forest management. Economic valuation provides basis for payment for ecosystem services (PES). Therefore, objective of this study was to evaluate eco-tourism and carbon stock services of the Maindam valley, District Swat, Pakistan. For the carbon stock calculation, a sample size of 155 plots of 0.1 hectare (Ha) was taken using preliminary survey at 95% confidence interval and 10% allowable error. The data for tourism services was collected from owners of all the hotels, 100 tourists and key informants of the area at 10% sampling intensity on pretested questionnaire for twenty years period (1997-2017). Results showed that Miandam valley has carbon stock worth US$ 16,306,000 while the value of eco-tourism was US$ 1,578,458 on annual basis. The results also showed that trend of tourism has drastically declined after the 9/11 incident for foreigners and locals and the situation was further deteriorated during the era of Talibanization or militancy from 2008-2011. This study recommends implementation of PES strategy at the rate of 5%, thus a total of US$ 78,922 can be earned from eco-tourism and carbon crediting in the study area annually, which could play important role in sustainable forest management.